Determinan pengungkapan corporation social responsibility (CSR) memasuki era pandemi COVID-19 - Molkend Siringoringo; Tiolina Evi (President University Press, 2023)
Disclosure of Corporate Social Responsibility entering the COVID-19 pandemic era has become one of the important issues in Indonesia. Therefore, this research objective is to provide an analysis of the determinants of the disclosure of corporate social responsibility The data collection technique in this research used a purposive sampling technique with 22 consumer goods sector companies in 2019-2021. The analysis method used is multiple linear regression model. This research provides analysis results of company size influencing corporate social responsibility disclosure, profitability has no influence on corporate social responsibility disclosure, leverage influences corporate social responsibility disclosure but positively. This research focuses on the level of corporate social responsibility disclosure entering the COVID-19 pandemic era, and discusses company size, profitability including leverage in consumer goods sector companies.